Influence of long-term supplementation of a formulated botanical blend on growth performance and carcass traits in feedlot steers - Thiago Lauro Maia Ribeiro; Becca B. Grimes Francis; Erin R. DeHaan; Cassidy R. Ross; Justin J. Delver; Forest L. Francis; Jeff S. Heldt; Emma H. Wall; Warren C. Rusche; Zachary K. Smith (Animal Bioscience)
Objective The objective of this study was to determine if a formulated blend of capsicum oleoresin, clove essential oil, and garlic essential oil (Fytera Advance - Selko USA, Indianapolis IN, USA; CCG) influences measures of cattle growth, efficiency, or carcass traits, during the finishing phase in steers fed a concentrate-based diet. Methods Charolais×Angus steers (n = 96; initial shrunk body weight [BW] = 391±34.0 kg) were used in a 144-d (16 February 2023 to 9 July 2023) finishing feedlot experiment in Brookings, SD, USA. Steers were individually weighed and allotted to one of 14 pens (6 to 7 steers; 7 pens/treatment) in a randomized complete block design and randomly assigned to 1 of 2 treatments: control diet without the test product (CON) or a diet including CCG at 500 mg/steer daily (CCG). Steers were fed twice daily, and bunks were managed according to a slick bunk system. Results There were no differences (p≥0.10) in any growth performance outcomes from d 1 to 35, 36 to 70, or 71 to 98. From d 99 to 144 steers from CCG tended to have 5% greater average daily gain (p = 0.09) and 8% improved feed conversion (G:F) (p = 0.01). No differences (p≥0.15) were noted for cumulative growth performance measures. No differences were noted for any carcass measurements or categorical carcass outcomes, nor lung or liver health outcomes (p≥0.15). Conclusion The use of CCG had no influence on cumulative growth performance responses. However, the use of CCG improved G:F during the late feeding period.